Assessing the Effects of Music on Anxiety and Performance in Tasks Using Heart Rate Variability and Mean Arterial Pressure - M. Nithya Mylakumar (22155802) (2024)
Anxiety disorder affects 264 million people worldwide. According to the Anxiety and Depression Association of America, 31% of the population experiences anxiety problems at some point in time. There are more than 18% of people with anxiety disorder in India. This negatively impacts their ability to focus on their daily tasks. Music can be used as a tool to improve the quality of life for those who have difficulties carrying out day-to-day tasks. In this study, 20 subjects with severe anxiety disorders were assessed using the Hamilton Anxiety Rating Scale (HAM-A) are participated. The subjects were divided into two groups based on their musical preferences (Kaapi and weightless). The effect of music (weightless music and Kaapi raga) on cardiovascular parameters in anxiety disorders participants was examined while listening to music and performing an attention-based task by measuring electrocardiogram (ECG) and Mean Arterial Pressure (MAP). A comparison of MAP between weightless music and the Kaapi group did not show statistically significant differences, however, changes were noted within both groups. Listening to music (task 1) significantly altered the Time domain Heart Rate Variability (HRV), RMSSD(Root Mean Square of Successive Differences) and TINN (Triangular Index) for the Kaapi group. In comparison to task performance without music and with weightless music, omission, and commission errors were significantly reduced (p =0.012). However, there was no significant difference between Tasks 2 (performing tasks in silence) and 3 (performing tasks with music) in omission or commission errors among the Kaapi group. RMSDD has been increased by Kaapi raga, thereby increasing heart rate variability, and reducing anxiety. This raga may be used as an intervention for participants with anxiety disorders. A weightless sound is effective in improving attention when a task needs to be accomplished. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2024.3464129